Norms among heterogeneous agents: a rational-choice model - Karol B. Zdybel (University of Hamburg, Institute of Law and Economics (ILE), 2024)
Spontaneous norms, or simply norms, can be defined as rules of conduct that emerge without intentional design and in the absence of purposeful external coordination. While the law and economics scholarship has formally analyzed spontaneous norms, the analysis has typically been limited to scenarios where agents possess complete information about the interaction structure, including others' understanding of desirable and undesirable outcomes. In contrast, this paper examines spontaneous norms under the assumption of agent heterogeneity and private preferences. By employing a game-theoretical framework, the analysis reveals that norms' lifecycle can be divided into a formative phase and a long-run phase. The formative phase crucially shapes the norm's content and is itself critically dependent on the initial beliefs that agents hold about each other. Moreover, spontaneous norms are resilient to minor shocks to the belief structure but disintegrate when the magnitude of shocks becomes significant. In the final part, the paper highlights the broader implications of its findings, indicating applications in general law and economics, legal anthropology and history, and the sociology of social norms.
Keywords: K00; K10; K39; P48; Z13; 330; Spontaneous norms; Social norms; Custom; Private assessment; Legal history